Anisotropic and amphoteric characteristics of diverse carbenes. Issue 20 (23rd March 2018) - Kim, Dong Yeon; Yang, D. ChangMo; Madridejos, Jenica Marie L.; Hajibabaei, Amir; Baig, Chunggi; Kim, Kwang S.
Abstract : The singlet/triplet stabilities and amphoteric behaviors of diverse carbenes are elucidated with the anisotropic natures of their electron configurations. Abstract : Despite its key importance in carbene chemistry, the amphoteric ( i.e., both nucleophilic and electrophilic) behavior of the divalent carbon atom (:C) in carbenes is not well understood. The electrostatic potential (EP) around :C is often incorrectly described by simple isotropic atomic charges (particularly, as in singlet CF2 ); therefore, it should be described by the multipole model, which can illustrate both negative and positive EPs, favoring the positively and negatively charged species that are often present around :C. This amphotericity is much stronger in the singlet state, which has more conspicuous anisotropic charge distribution than the triplet state; this is validated by the complexation structures of carbenes interacting with Na +, Cl −, H2 O, and Ag + . From the study of diverse carbenes [including CH2, CLi2 /CNa2, CBe2 /CMg2, CF2 /CCl2, C(BH2 )2 /C(AlH2 )2, C(CH3 )2 /C(SiH3 )2, C(NH2 )2 /C(PH2 )2, cyclic systems of C(CH2 )2 /C(CH)2, C(BHCH)2, C(CH2 CH)2 /C(CHCH)2, and C(NHCH)2 /C(NCH)2 ], we elucidate the relationships between the electron configurations, electron accepting/donating strengths of atoms attached to :C, π conjugation, singlet–triplet energy gaps, anisotropic hard wall radii, anisotropic electrostatic potentials, and amphotericities of carbenes, which are vital to carbene chemistry. The (σ 2, π 2 or σπ) electronic configuration associated with :C on the :CA2 plane (where A is an adjacent atom) in singlet and triplet carbenes largely governs the amphoteric behaviors along the :C tip and :C face-on directions. The :C tip and :C face-on sites of σ 2 singlet carbenes tend to show negative and positive EPs, favoring nucleophiles and electrophiles, respectively; meanwhile, those of π 2 singlet carbenes, such as very highly π-conjugated 5-membered cyclic C(NCH)2, tend to show the opposite behavior. Open-shell σπ singlet (such as highly π-conjugated 5-membered cyclic C(CHCH)2 ) and triplet carbenes show less anisotropic and amphoteric behaviors.